Novel mutations in dystonin provide clues to the pathomechanisms of HSAN-VI. (30th May 2017) - Manganelli, Fiore; Parisi, Silvia; Nolano, Maria; Tao, Feifei; Paladino, Simona; Pisciotta, Chiara; Tozza, Stefano; Nesti, Claudia; Rebelo, Adriana P.; Provitera, Vincenzo; Santorelli, Filippo M.; Shy, Michael E.; et al.
Abstract : Objective: To describe a second hereditary sensory autonomic neuropathy type VI (HSAN-VI) family harboring 2 novel heterozygous mutations in the dystonin ( DST ) gene and to evaluate their effect on neurons derived from induced pluripotent stem cells (iPSC). Methods: The family consisted of 3 affected siblings from nonconsanguineous healthy parents. All members underwent clinical and electrophysiologic evaluation and genetic analysis. Two patients underwent quantitative sensory testing (QST), cardiovascular reflexes, dynamic sweat test, and skin biopsy to evaluate somatic and autonomic cutaneous innervation and to get fibroblast cultures for developing iPSC-derived neurons. Results: Onset occurred in the first decade, with painless and progressive mutilating distal ulcerations leading to amputation and joint deformity. Sensation to pain, touch, and vibration was reduced. Autonomic disturbances included hypohidrosis, pupillary abnormalities, and gastrointestinal and sexual dysfunction. Nerve conduction studies showed a severe axonal sensory neuropathy. QST and autonomic functional studies were abnormal. Skin biopsy revealed a lack of sensory and autonomic nerve fibers. Genetic analysis revealed 2 pathogenic mutations in the DST gene affecting exclusively the DST neuronal isoform-a2. Neurons derived from iPSC showed absence or very low levels of DST protein and short and dystrophic neuritis or no projections at all. Conclusions: Unlike the previous HSAN-VI family, our description indicates that DST mutations may be associated with a nonlethal and nonsyndromic phenotype. Neuronal loss affects large and small sensory nerve fibers as well as autonomic ones. Induced-PSC findings suggest that dystonin defect might alter proper development of the peripheral nerves. Dystonin-a2 plays a major role in the HSAN-VI phenotype.